Successful management of thrombocytopenia by partial splenic embolization in patients with advanced gastric cancer and invasion of the splenic vein: Case reports. Issue 28 (16th July 2021) - Nakatsubo, Ryosuke; Yamauchi, Yoshiya; Hiraizumi, Taisho; Naruse, Fumi; Kanda, Ryoya; Suzuki, Yuka; Kakegawa, Tatsuya; Kurosawa, Takashi; Yoshimasu, Yu; Saguchi, Toru; Sofuni, Atsushi; Itoi, Takao
Abstract: Rationale: Hypersplenism causes thrombocytopenia, which may lead to the reduction or discontinuation of chemotherapy. Partial splenic embolization (PSE) is an effective treatment for thrombocytopenia associated with hypersplenism. However, there have been no reports of patients with gastric cancer who have resumed and continued chemotherapy after PSE for splenic hypersplenism associated with tumor infiltration. Here, we report two cases in which we performed PSE for hypersplenism associated with gastric cancer that had invaded the splenic vein. Chemotherapy was continued in both cases. Patient concerns: Both patients developed thrombocytopenia with splenomegaly due to advanced gastric cancer that required discontinuation of chemotherapy. Diagnosis: Upper gastrointestinal endoscopy and computed tomography showed advanced gastric cancer with invasion of the splenic vein and splenomegaly. Both patients developed thrombocytopenia. Interventions: Patients were treated with PSE. Outcomes: PSE produced an increase in thrombocyte count, and chemotherapy could be resumed. Lessons: PSE seems to be a useful treatment for thrombocytopenia with splenomegaly associated with advanced gastric cancer and may allow continuation of chemotherapy.